Subtitle translation for stand-up comedies : strategies and challenges for humour translation - Lu, Zhipeng (Nanyang Technological University, 2020)
Irony and verbal humour play an important role in entertainment and interaction. People criticize and complain by means of irony and satire, using jokes to generalize and expressing culture and way of thinking. The main aim of this paper is to classify the different types of humour in stand-up comedies and provide corresponding translation rationale and strategies. This paper applied the semantic and pragmatic theories for the analysis of humour and translation of humour are reviewed and applied in the discussion of the translation results. The examples are from stand-up comedy recordings in YouTube. The classifications of the humour types and translation strategies applied for different translation effects are hoped to serve as references for translation practitioners who are interested in developing skills in humour translation.